2021
DOI: 10.1111/mcn.13135
|View full text |Cite
|
Sign up to set email alerts
|

Women's fasting habits and dietary diversity during Ramadan in rural Bangladesh

Abstract: Little is known about fasting practices and dietary changes during Ramadan in lowand lower-middle-income countries. Although pregnant women are exempt from fasting, they may still fast. This is of interest as dietary habits during pregnancy may affect the development of the unborn child. In a community-based sample of young women in rural Sylhet division, Bangladesh, we described fasting practices and beliefs (n = 852). We also examined reported food group consumption and minimally adequate dietary diversity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
(42 reference statements)
1
26
0
Order By: Relevance
“…It was found that among the urban population, the overall consumption rate of packaged items was higher than the rural population. The percent intake of puffed rice, fried food (peyaju, beguni, jilapi), and branded ice creams were significantly high during Ramadan as compared to the non-Ramadan period (p<0.05).In a study on dietary habits among women during Ramadan season in the Sylhet division of Bangladesh, consumption of fatty foods and sweets was found to be 97.5% and 89.3% higher respectively as compared to the non-Ramadan period (Seiermann et al, 2021). Along with the increasing income and productivity, the Bangladeshi population has become busier and more urbanoriented during the last decade.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that among the urban population, the overall consumption rate of packaged items was higher than the rural population. The percent intake of puffed rice, fried food (peyaju, beguni, jilapi), and branded ice creams were significantly high during Ramadan as compared to the non-Ramadan period (p<0.05).In a study on dietary habits among women during Ramadan season in the Sylhet division of Bangladesh, consumption of fatty foods and sweets was found to be 97.5% and 89.3% higher respectively as compared to the non-Ramadan period (Seiermann et al, 2021). Along with the increasing income and productivity, the Bangladeshi population has become busier and more urbanoriented during the last decade.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a study reported no difference in energy and nutrient intakes of young women during Ramadan fasting despite the decrease in the number of meals [ 19 ]. Another study in individuals with type 2 diabetes noted that total energy, energy from carbohydrates, and protein intake after Ramadan fasting were similar to those before Ramadan, while energy from fat intake of individuals increased [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite Quran exempting pregnant and lactating women from participating in Ramadan fasting, in most cultures, they prefer to fast [1,2]. Previous research shows that between 70% to 90% of Muslim women, including pregnant mothers, participate in fasting for some days during the Ramadan month [3,4,5,6]. Thus, Ramadan fasting will overlay with pregnancy in three out of four births which roughly accounts for more than 1 billion Muslims alive today who had in-utero exposure to Ramadan [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, based on a prospective cohort study among schooling Ghanaian adolescents who fasted during Ramadan, Ali and Abizari [20] reported that fasting made marked changes in typical food patterns and helped to improve dietary diversity. Similarly, the evidence from rural Bangladesh suggests that exposure to Ramadan helps to increase dietary quality in both fasting and non-fasting Muslim women [3].…”
Section: Introductionmentioning
confidence: 99%